Discontinuous video recording of biopsies in the context of an integral third degree teaching program - Rodríguez José (BMC, 2008)
Abstract Background The application of Information and Communication Technologies (ICTs) in the field of university education can play an important role in order to fulfil the objectives of the European Space for Higher Education (ESHE). In the absence of an infrastructure that allows virtual preparations, the high definition video may become an alternative for many PC users and telepathology enthusiasts. Methods We have begun a video biopsy discontinuous recording pilot programme, also known as interval cinematography, in order to give our students pathological images to gather documentary evidence to follow their clinical cases. We have a working post available with a ZEISS Axioshop 2 microscope connected to a JVC digital camera with a double output for video, a PVM_14N1MDE Sony Triniton colour monitor and a LG RH199 HDD-DVD recorder. Results Pathologists can easily produce videos lasting between 45" and 5' according to the case. Later those videos are assessed all together and given to the student and/or the doctor who requested the case study. Conclusion Better follow-up studies of the cases can be achieved using Discontinuous video recording of biopsies. This approach has also clinical benefits since it contributes to the enrichment of integral patient care.